Pengaruh Kemampuan Pemahaman Konsep, Kemampuan Komunikasi dan Koneksi Terhadap Kemampuan Pemecahan Masalah - Hartati, Sri; Abdullah, Ilham; Haji, Saleh (Mathematics Education Journal, 2017)
This research aims to determine the influence of concept understanding ability (X1), communication ability (X2) and mathematical connection ability (X3) on problems solving ability (Y); the influence of concept understanding ability (X1) on communication ability (X2); the influence of concept understanding ability (X1) on mathematical connection ability (X3); and communication ability (X2) on connection ability (X3). This research is a survey research with quantitative approach. Population of the research is the students of second grade Public Junior High School 1 of Padang Jaya. The sample is taken by using non-probability sampling method using saturated sampling. Data is analyzed by using Path Analysis with 5% significance level. The research result shows that (1) concept understanding ability (ρyx1X1 = 0,374), communication ability (ρyx2X2 = 0,181 and connection ability (ρyx3X3 = 0,201) give influence on problems solving ability; (2) the concept understanding ability (ρx2x1X1= 0,323) gives influence on communication ability; (3) concept understanding ability (ρx3x1X3 = 0,442) gives influence on connection ability and (4) communication ability (ρx3x2X3 = 0,470) give influence on connection ability.